2017
DOI: 10.1371/journal.pone.0170126
|View full text |Cite
|
Sign up to set email alerts
|

Novel Porcine Epidemic Diarrhea Virus (PEDV) Variants with Large Deletions in the Spike (S) Gene Coexist with PEDV Strains Possessing an Intact S Gene in Domestic Pigs in Japan: A New Disease Situation

Abstract: Since late 2013, after an absence of seven years, outbreaks of porcine epidemic diarrhea virus (PEDV) infection have reemerged and swept rapidly across Japan, resulting in significant economic losses. In this study, we report the emergence, mixed infection, and genetic characterization of 15 novel field PEDV variants with large genomic deletions. The sizes of deletion varied between 582 nt (194 aa) and 648 nt (216 aa) at positions 28–714 (10–238) on the S gene (protein). Among 17 PEDV samples isolated from ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 47 publications
2
52
1
Order By: Relevance
“…This finding suggests that S1 NTD-del PEDV had no replication advantage and was either outcompeted or coexisted with Sintact PEDV in pigs. This conclusion is in agreement with what were observed in the field (Diep et al, 2017;Su et al, 2018). S1 NTD-del PEDV replicated to a lower peak titer in coinfection than that in single virus infection in both Vero cells and IPEC-DQ cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding suggests that S1 NTD-del PEDV had no replication advantage and was either outcompeted or coexisted with Sintact PEDV in pigs. This conclusion is in agreement with what were observed in the field (Diep et al, 2017;Su et al, 2018). S1 NTD-del PEDV replicated to a lower peak titer in coinfection than that in single virus infection in both Vero cells and IPEC-DQ cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, our laboratory isolated the first S1 NTD-del PEDV strain, PC177, from Vero cell culture (Oka et al, 2014). Recent studies revealed that S1 NTD-del PEDVs naturally evolved in the field and often coinfected pigs with the S-intact PEDV (Suzuki et al, 2015;Diep et al, 2017;Zhang et al, 2018a;Su et al, 2018). The S1 NTD-del PEDV had no tissue tropism change compared with the S-intact PEDV (Suzuki et al, 2016;Hou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR conditions were as follows: denaturation at 94°C for 2 min; 35 cycles of denaturation at 98°C for 10 s, annealing at 55°C for 30 s, and extension at 68°C for 2.5 min; and a final extension step at 68°C for 10 min. Then, the PCR products were used as templates for nested PCR to amplify five DNA fragments spanning the entire S gene using five published primer pairs (CS1–CS5) (Diep, Norimine, Sueyoshi, Lan, & Yamaguchi, ). The amplified PCR products were purified using a FastGene Gel/PCR Extraction Kit (NIPPON Genetics Co., Ltd, Japan) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In October 2013, however, a PED outbreak was reported in Japan (Okinawa Prefecture) after an interval of 7 years when there were no infestations reported (Sasaki et al, 2016). The epidemic of PED virus infection spread rapidly throughout Japan (Diep et al, 2017) and was also reported in Kagoshima prefecture, which has the largest number of pig farms in Japan. In Kagoshima, a numbers of farms produce pork from Kagoshima Berkshire pigs ('Kagoshima Kurobuta') which is one of the most sought pork brands in Japan.…”
Section: Introductionmentioning
confidence: 99%